Respiratory depression in women receiving propofol/esketamine versus propofol/fentanyl for abortion surgery or curettage: a randomized clinical trial - Cuiwen Zhang; Jiaxin Luo; Yeqing Liao; Huiyu Cao; Xiaoshan Wu; Xiaofang Huang; Hongmeng Lan; Yuliu Lin; Huihe Chen; Xuehai Guan (Annals of Medicine)
Background A combination of opioids with propofol is a popular approach to non-intubated general anaesthesia; however, this method usually results in higher incidence of respiratory depression. We compared the incidence of esketamine- and fentanyl-induced respiratory depression in women undergoing abortion surgery or curettage under propofol-based non-intubated general anaesthesia.Methods This study included 176 women (aged 18–60 years) scheduled for abortion surgery or curettage. Patients were randomized into the fentanyl or esketamine groups. Patients in the fentanyl group received fentanyl (1 µg/kg) combined with propofol intravenously. Patients in the esketamine group received subanaesthetic doses of esketamine (0.15 mg/kg) combined with propofol intravenously. The primary outcome was the incidence of respiratory depression during anaesthesia. Secondary outcomes included respiratory rate, pulse oximetry, blood pressure, heart rate, propofol dose, duration of surgery, duration of anaesthesia, and adverse events.Results The incidence of respiratory depression in the esketamine group was significantly lower than that in the fentanyl group (11% vs. 45%; p < .0001). Propofol administration was lower with esketamine than fentanyl. Respiratory rate, SpO2 and blood pressure were more stable in the esketamine group than in the fentanyl group. The incidences of hypotension, propofol-induced injection pain and chin lifting in the esketamine group were lower than those in the fentanyl group. The incidence of nightmares was higher in the esketamine than in the fentanyl group.Conclusions The incidence of respiratory depression was lower with subanaesthetic doses of esketamine than with fentanyl in women undergoing abortion surgery or curettage under propofol-based non-intubated general anaesthesia.KEY MESSAGESOpioids combined with propofol is a popular method for non-intubated general anaesthesia; however, this method usually results in higher incidence of respiratory depression.At subanaesthetic doses, esketamine provides an analgesic effect by antagonizing the N-methyl-d-aspartate receptor.In this trial, the incidence of respiratory depression was lower with subanaesthetic doses of esketamine than with fentanyl in women undergoing abortion surgery or curettage under propofol-based non-intubated general anaesthesia.